KARAKTERISTIK BRIKET BIOARANG CAMPURAN LIMBAH SERBUK KAYU SUNGKAI (Peronema canascens Jack.) DAN SEKAM PADI (Oryza sativa) - Yudian Noorhakim; Sunardi Sunardi; Henny Arryati (Jurnal Sylva Scienteae, 2020)
Making briquettes from biomass feedstocks is expected to address environmental concerns as well as a solution to the scarcity of fuel. One type of waste that is produced is a lot of sawdust powder one of which sanggai sawdust powder type other than that which is not less generated is rice husk waste. Where from the two raw materials can be processed into charcoal briquettes. The objectives of this research are to know the characteristics of borang mixture of sungkai wood powder and rice husk, including: water content, density, ash content, airborne content, carbon content and calorific value. In addition to knowing the quality of charcoal briquette quality produced compared to the standard include: ASTM, SNI, JAS and BSI. This research used raw material of sungkai wood powder and rice husk with 3 replications and 5 treatments, namely: 100% sungkai wood powder, 75% sungkai wood powder: 25% rice husk, 50% sungkai wood powder: 50% rice husk, 25% Sungkai wood powder: 75% rice husk and 100% rice husk using 10% tapioca adhesive. Variation of charcoal briquettes mixture of sungkai wood powder waste and rice husk in making charcoal briquettes have significant effect on water content, ash content, content of fly content, bound carbon content and calorific value. The results showed that water content meets ASTM standards but does not meet SNI, JAS and BSI standards. Airborne content meets ASTM and JAS standards but, does not meet SNI and BSI standards. While the rest for density, ash content, bound carbon content and heating value all do not meet the standards of ASTM, SNI, JAS and BSI.Keywords: Characteristic of bioarang briquettes; Sungkai wood charcoal; Rice husk charcoal